2013
DOI: 10.1371/journal.pone.0067342
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Instability in Liver Cells Caused by an LPS-Induced Bystander-Like Effect

Abstract: Bacterial infection has been linked to carcinogenesis, however, there is lack of knowledge of molecular mechanisms that associate infection with the development of cancer. We analyzed possible effects of the consumption of heat-killed E. coli O157:H7 cells or its cellular components, DNA, RNA, protein or lipopolysaccharides (LPS) on gene expression in naïve liver cells. Four week old mice were provided water supplemented with whole heat-killed bacteria or bacterial components for a two week period. One group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…They showed that not all cell lines released histones from nucleosomes during DNA fragmentation and apoptosis, while Gabler et al [32] demonstrated that the cytoplasmic accumulation of histones and nucleosomes in physiological cells was a precursor to apoptosis, occurring in parallel with the initial phagocytosis signals. During microglia activation by LPS, for instance, DNA damage and genome instability were observed [52,53]. Unmodified H2B in the cytoplasm acts as a sensor that detects double-stranded DNA fragments derived from infectious agents or damaged cells and as a consequence activates innate and acquired immune responses in various cell types [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that not all cell lines released histones from nucleosomes during DNA fragmentation and apoptosis, while Gabler et al [32] demonstrated that the cytoplasmic accumulation of histones and nucleosomes in physiological cells was a precursor to apoptosis, occurring in parallel with the initial phagocytosis signals. During microglia activation by LPS, for instance, DNA damage and genome instability were observed [52,53]. Unmodified H2B in the cytoplasm acts as a sensor that detects double-stranded DNA fragments derived from infectious agents or damaged cells and as a consequence activates innate and acquired immune responses in various cell types [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The LPS-stimulated biological effect on p53-induced apoptosis in the liver [53,54] surpasses the effect of Sirt1 as to the deacetylation of p53, reducing the hepatic lipid turnover. Hence, the p53-mediated downregulation of PXR activity [55,56] is not dependent of the Sirt1/PXR-mediated reactions [57][58][59][60].…”
Section: Lps Modulation Of Sirt1/p53 Interactions Is Coupled To Fat Imentioning
confidence: 94%
“…Sirt1 and its posttranscriptional impact on p53 [42,43] is heavily involved in the differentiation of adipocytes, as well as lipid metabolism in general [44][45][46][47][48], with their implications for abnormal Sirt1 deacetylation of p53, linked to lipid metabolism with its characteristic transformation of adipocytes and ensuing liver disease. Interestingly, both Sirt1 and p53 knockout mice develop NAFLD [49][50][51][52], which alludes to a close connections between adipocyte phenotype "switch" involving Sirt 1 and/or p53 impact on mitochondrial functioning [53][54][55][56].…”
Section: Food Restriction Organ Crosstalk In Obese/diabetic "Mice Andmentioning
confidence: 99%
“…LPS induction of APPs are linked to the CD14 receptor with the levels linked to liver inflammation and NAFLD [31]. LPS has been shown to effect hepatic genomic stability [32] with effects on reverse cholesterol transport in macrophages [4] and with macrophage activation [33]. LPS can rapidly insert into cell membranes with a preference for insertion and partition into cholesterol/ sphingomyelin domains in cell membranes [34]- [36].…”
Section: Lps Neutralize Apo E Binding To Membrane Lipids With Effectsmentioning
confidence: 99%